Moisture sorption isotherms for crushed chillies - Arslan, N; Togrul, H (Academic Press Inc Elsevier Science, 2005)
The moisture isotherms of crushed chillies stored in a chamber the relative humidity of which is controlled by an atomising humidifier were determined at 25, 35 and 45 degreesC and within the range of 0.1-0.8 water activity. The sorption isotherms of crushed chillies exhibited type III behaviour according to BET classification. Sorption capacity decreased with increasing temperature. The sorption isotherms of crushed chillies exhibited hysteresis. The moisture sorption data were used to fit Guggenheim-Anderson-de Boer, Brunauer-Emmett-Teller, Henderson, Oswin, Peleg, Crapiste and Rotstein, Caurie models, and constants of equations tested were determined by non-linear regression analysis. Among the various models tested to interpret sorption isotherms, one was selected which presented best statistical indicators. The Peleg and the Crapiste-Rotstein models correctly fit the whole set of data, for water activity ranging from 0.1 to 0.8, but the Crapiste and Rotstein model was preferred since the values of its parameter were more realistic. The surface area of the monolayer was calculated. The water activities corresponding to the monolayer values were determined. The thermodynamic functions such as isosteric heat of sorption, sorption entropy, spreading pressure, net integral enthalpy and entropy were determined by means of sorption isotherm data. The isosteric heats of desorption, calculated from the slope of plot of logarithm of water activity versus reciprocal of temperature, were higher than the isosteric heats of adsorption. (C) 2004 Silsoe Research Institute. All rights reserved Published by Elsevier Ltd.
Keywords: Enthalpy-Entropy Compensation; Thermodynamic Properties; Desorption Isotherms; Starch Powders; Water; Equilibrium; Temperature; Adsorption; Equations; Models